PERAN KEPALA SEKOLAH DALAM IMPLEMENTASI KURIKULUM OPERASIONAL SEKOLAH PENGGERAK DI TAMAN KANAK-KANAK MUSLIMAT 06 LANJI KECAMATAN PATEBON KABUPATEN KENDAL - Nur Hidayah; Titik Haryati; I Made Sudana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research is based on the phenomenon of Muslimat 06 Lanji Kindergarten which has the advantage of being the only driving school in Patebon sub-district. So the School Operational Curriculum used is the Merdeka curriculum. This success certainly cannot be separated from the role of the school principal. The aims of this research are: 1) To describe and analyze the role of the principal as a manager in implementing the driving school operational curriculum at Muslimat 06 Lanji Kindergarten, 2) To describe and analyze the role of the school principal as an entrepreneurial developer in implementing the driving school operational curriculum at Muslimat 06 Lanji Kindergarten, and 3) Describe and analyze the role of the principal as supervisor in implementing the driving school operational curriculum at Muslimat 06 Lanji Kindergarten. Study this is annoying approach qualitative with a case study at TK Muslimat 06 Lanji subdistrict Patebon , done on month July-August 2023. Step study includes : 1) compiling plan research , 2) choose field research , 3) take care of licensing , 4) Exploring And evaluate field , 5) Choose And utilise information , 6) Prepare equipment research . Instrument study This is researcher yourself . Technique data collection : interviews , observations , And documentation . Technique analysis of the data used is interactive model from Miles, Huberman which includes : collection data ,condensation data, data presentation and withdrawal conclusion . Checking validity of the data used test credibility , transferability , dependability , and confirmability . The results of the research show that: (1) The role of the principal as manager has been carried out well by the principal, with curriculum planning and development, a clear vision and mission, resource management and monitoring the effectiveness of the curriculum although several obstacles are still found in resource management (2 ) The role of the school principal as an entrepreneurial developer has been carried out through market days. (3) The principal's role as supervisor has also been carried out well, namely preparing supervision plans, regularly assessing teacher performance and evaluating the results of teacher performance assessments as well as following up on evaluation results. Based on the results of the research that has been carried out, it can be concluded that the role of the principal in implementing the operational curriculum of the Driving School at Muslimat 06 Lanji Kindergarten has been implemented well.